Understanding rangeland desertification through pastoralist perspectives using a grounded theory approach - Mohsen Sharaftmandrad; Mohammadreza Shahraki (Scientific Reports)
Abstract Rangeland desertification risk has significantly increased due to the fragility of these ecosystems and the severity of degradation caused by climate instability and human activities over the last decade. This research focuses on identifying indicators of rangeland desertification risk using a qualitative grounded theory approach based on the perspectives of pastoralists in Kolijah and Qolaq-Borte, Golestan Province, Iran. The study population comprised regional pastoralists, with 15 experts selected through snowball sampling. Data collection was conducted through in-depth, semi-structured interviews, with thematic analysis carried out via open, axial, and selective coding. Results revealed three primary categories of desertification indicators: “vegetation,” “employment and income sources,” and “climate and natural hazards,” scoring 3.08, 3.00, and 2.80, respectively. Meanwhile, “water and water resources,” “animal health and diseases,” and “participation and social capital” were identified as less significant. Key findings emphasize the importance of vegetation decline, with reduced forage quality and increased prevalence of unpalatable plants serving as prominent signs of desertification. Additionally, socio-economic impacts, including increased animal husbandry costs and reduced livelihood resilience, highlight the multifaceted nature of desertification risk. The study underscores the critical need for targeted conservation policies, incorporating local knowledge to enhance restoration and sustainable management practices. By identifying the key indicators and their impacts, this research provides valuable insights for mitigating desertification and promoting the resilience of rangelands and pastoralist communities.